h - Koutny, Maciej; Ulidowski, Irek.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed proceedings of the 23rd International Conference on Concurrency Theory, CONCUR 2012, held in Newcastle upon Tyne, UK, September 4-7, 2012. The 35 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 97 submissions. The papers are organized in topics such as reachability analysis; qualitative and timed systems; behavioural equivalences; temporal logics; session types; abstraction; mobility and space in process algebras; stochastic systems; probabilistic systems; Petri nets and non-sequential semantics; verification; decidability.
Reachability analysis.-qualitative and timed systems.-behavioural equivalences.-temporal logics.-session types -- abstraction -- mobility and space in process algebra.-stochastic systems.-probabilistic systems -- Petri nets and non-sequential semantics.-verification; decidability.
Keywords: Computer science; Computer communication systems; Software engineering; Programming languages (Electronic computers).; Computer logic; Mathematical logic; Computer Science; Software Engineering; Logics and Meanings of Programs; Computer Communication Networks; Programming Languages, Compilers, Interpreters; Information Systems Applications (incl. Internet).; Mathematical Logic and Formal Languages; Electronic books